2021
DOI: 10.1093/bbb/zbab086
|View full text |Cite
|
Sign up to set email alerts
|

Tectorigenin attenuates cognitive impairments in mice with chronic cerebral ischemia by inhibiting the TLR4/NF-κB signaling pathway

Abstract: This study aims to explore the effect of Tectorigenin in chronic cerebral ischemia (CCI)-induced cognitive impairment mice model. Cognitive impairment, hippocampal tissue histopathology and myelin density in CCI mice were detected. HT22 cells were used to induce oxygen-glucose deprivation/reperfusion (OGD/R) injury. Cells viability and apoptosis of transfected HT22 cells, toll-like receptor-4 (TLR4)/Nuclear factor-kappaB (NF-κB) pathway-related factors levels in hippocampal tissue and OGD/R models were detecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Inhibition of myocardial cell apoptosis appears to be the mechanism operating in anti-myocardial ischemia/reperfusion injury [14]. Tectorigenin has been shown to repress oxygen-glucose deprivation/reperfusion-induced apoptosis in HT22 cells, thereby ameliorating chronic cerebral ischemia [11]. The results of this study also showed that tectorigenin enhanced cell viability and reduced the apoptosis of hypoxia/reoxygenation-induced H9c2 cells, leading to improvement in myocardial cell apoptosis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Inhibition of myocardial cell apoptosis appears to be the mechanism operating in anti-myocardial ischemia/reperfusion injury [14]. Tectorigenin has been shown to repress oxygen-glucose deprivation/reperfusion-induced apoptosis in HT22 cells, thereby ameliorating chronic cerebral ischemia [11]. The results of this study also showed that tectorigenin enhanced cell viability and reduced the apoptosis of hypoxia/reoxygenation-induced H9c2 cells, leading to improvement in myocardial cell apoptosis.…”
Section: Discussionsupporting
confidence: 54%
“…Oxygen-glucose deprivation/reperfusion-induced apoptosis and inflammation in HT22 cells are suppressed by tectorigenin, and tectorigenin ameliorates cognitive impairments and chronic cerebral ischemia [11]. Therefore, tectorigenin might also exert a protective effect against myocardial ischemia/reperfusion injury.…”
Section: Introductionmentioning
confidence: 99%
“…Tectorigenin was also reported as a lactate dehydrogenase (LDH) inhibitor from several Chinese medicinal herbs by UF-HPLC-DAD-MS [151]. The protective mechanism of tectorigenin was related to oxidative stress and inflammation in which phosphoinositide 3-kinase (PI3K)/AKT, TLR4/NF-κB, PPARγ/NF-κB pathways were involved [39,152,153]. Chen et al [39] revealed that tectorigenin effectively prevented HUVECs from H 2 O 2 -induced oxidative stress injury by upregulating the PI3K/AKT pathway.…”
Section: Cardioprotective and Cerebroprotective Effectsmentioning
confidence: 99%
“…Chen et al [39] revealed that tectorigenin effectively prevented HUVECs from H 2 O 2 -induced oxidative stress injury by upregulating the PI3K/AKT pathway. In addition, tectorigenin could alleviate cognitive impairment, hippocampal tissue and myelin damage, and inflammation of chronic cerebral ischemia mice [153]. In vitro, tectorigenin benefited HT-22 cell survival and protected against oxygen-glucose deprivation/reoxygenation (OGD/R) damage.…”
Section: Cardioprotective and Cerebroprotective Effectsmentioning
confidence: 99%
“…13,14 Tectorigenin attenuates cognitive impairment in mice with chronic cerebral ischemia by blocking the TLR4/NF-κB signaling pathway and inhibiting the NLRP3 inflammasome activity. 15 Tectorigenin could also prevent fulminant liver failure by restraining TLR4/MAPK and TLR4/NF-κB pathways and accelerating autophagy. 10 Furthermore, in skin disease therapy, tectorigenin can alleviate ultraviolet-induced skin damage.…”
Section: Introductionmentioning
confidence: 99%